Facile layered structure of sensing chip of a prism–based surface plasmon resonance device. (2022) - Joshi, Ashutosh; Manjuladevi, V.; Kumar Gupta, Raj
Graphical abstract: Abstract: Surface plasmon resonance (SPR) is a popular optical phenomenon for sensing application owing to its capability for label-free measurement which offers very high resolution and sensitivity. The traditional prism based Kretschmann configuration employs a sensing chip consists of a glass substrate deposited with 50 nm thick gold/silver layer. The parameters of the figure-of-merit (FOM) of an SPR sensor are a quality factor, signal-to-noise ratio, and the strength of the plasmonic field over the gold surface. In this article, we present a simulation work on a facile SPR sensor chip that yields a high FOM as compared to the traditional SPR sensor chip. We introduced a metallic intermediate layer (IML) in the traditional SPR chip and optimized the performance with respect to the material and thickness of IML. We optimized the thickness of the glass substrate such that the plasmonic field generated in the IML can couple with the outer gold film (OGF) . Such coupling enhances the overall plasmonic field over the OGF by 112%.